Relasi Self-Esteem dan Body Image dalam Terpaan Media Sosial Instagram - Michelia Martanatasha; Intan Primadini (ULTIMA Comm, 2019)
This research is motivated by the ‘social media detox' phenomenon, which is being carried out by many people to avoid the negative effect of social media. The high number of Instagram user, which is 80% of 150 billion active users in Indonesia can make people vulnerable to mental health problems as a result of the excessive use of social media Instagram. These problems are related to the perception of body image and the serious impact of self-esteem. The purpose of this research is to find out the impact of social media Instagram exposure on self-esteem levels through the perception of body image levels. This research used social comparison theory with the concepts of media exposure, body image, and self-esteem. The methodology of this research is quantitative with explanatory research. The respondents of this research were 400 respondents using non-probability purposive sampling technique by distributing online questionnaire. This research also used path analysis test to determine the indirect influence between the three variables. The result of this research shown that there is an indirect influence of social media Instagram exposure on self-esteem levels through the perception of body image levels. Also, there is a significant influence between social media Instagram exposure on the perception of body image levels by 7,6% and the perception of body image levels on self-esteem levels by 68,3%. However, between social media Instagram exposure and self-esteem levels do not have a significant effect. These results prove that the use of social media Instagram can influence the perception of their body image that also influence their self-esteem. Keywords: Body image, Instagram, Social Media, Self-esteem, Social Comparison Theory